Triplet combination of durvalumab, tremelimumab, and paclitaxel in biliary tract carcinomas: Safety run-in results of the randomized IMMUNOBIL PRODIGE 57 phase II trial. (January 2021) - Boilève, Alice; Hilmi, Marc; Gougis, Paul; Cohen, Romain; Rousseau, Benoît; Blanc, Jean-Frédéric; Ben Abdelghani, Meher; Castanié, Hélène; Dahan, Laëtitia; Tougeron, David; Metges, Jean-Philippe; Tournigand, Christophe; et al.
Abstract: Background: The IMMUNOBIL PRODIGE 57 trial is a non-comparative randomized phase II study assessing the efficacy and safety of the durvalumab (an anti-PD-L1) and tremelimumab (an anti-CTLA4) combination with or without weekly paclitaxel in patients with advanced biliary tract carcinoma (BTC) after failure of platinum-based chemotherapy. Taxanes have already been safely combined with immune checkpoint inhibitors in other tumors. We report results of the 20-patient safety run-in. Methods: Patients received durvalumab (1500 mg at day 1 [D1] of each cycle)/tremelimumab (75 mg at D1 for 4 cycles; Arm A) or durvalumab/tremelimumab with paclitaxel (80 mg/m 2 at D1, D8, D15; Arm B) every 28 days. Results: Twenty patients were enrolled (Arm A/B: 10/10). There were no dose-limiting toxicities (DLTs) in Arm A. Six DLTs were observed in five patients (50%) in Arm B, meeting a stopping rule for the trial inclusions. DLTs included three serious anaphylactic reactions (with one cardiac arrest), two enterocolitis, and one infectious pneumopathy with septic shock. There were no patients with history of personal or familial auto-immune disease. Conclusion: The safety run-in part of IMMUNOBIL PRODIGE 57 raised concerns regarding co-administration of paclitaxel with durvalumab and tremelimumab in BTC, with an unexpected increase in anaphylactic adverse events. Phase II of the study will only evaluate the durvalumab and tremelimumab combination arm. ClinicalTrials registration: NCT03704480 . Highlights: IMMUNOBIL phase II trial enrolls patients with advanced biliary tract cancers (BTC). Patients received durvalumab and tremelimumab with or without paclitaxel. With six dose-limiting toxicities in Arm B, a stopping rule was met. An unexpected increase in anaphylactic adverse events was observed. It raised concerns for durvalumab/tremelimumab combined with paclitaxel in BTC.